From barriers to solutions: an expert-based algorithm for cholangiocarcinoma and other biliary tract cancers testing in the Era of precision oncology - Stenzinger, Albrecht; Normanno, Nicola; Lamarca, Angela; Rimassa, Lorenza; Bibeau, Fréderic; Taniere, Philippe; Vogel, Arndt; Hollebecque, Antoine (Expert review of molecular diagnostics, 2025)
Biliary tract cancer (BTC) comprises a group of aggressive malignancies with poor prognosis and limited therapeutic options. Next-generation sequencing (NGS) has advanced BTC management by identifying targetable genomic alterations. However, routine multigene NGS testing faces clinical, logistical, and economic barriers to widespread implementation. A multidisciplinary panel of eight experts from Germany, France, the UK, Spain, and Italy convened to explore national challenges in NGS adoption and propose a structured molecular profiling approach. Discussions addressed pre-analytical tissue handling, sequencing strategies, and access limitations. Despite molecular advances, NGS access varies significantly across Europe. Barriers include suboptimal tissue sampling, restricted reimbursement, infrastructure gaps, and limited bioinformatics support. The panel recommends combined DNA and RNA sequencing as the ideal approach. In settings without NGS, referral to equipped centers is advised, with single-gene assays reserved for essential targets. This algorithm is a temporary yet practical guide to inform treatment decisions under current healthcare constraints, aiming to support equitable and informed care for BTC patients.